Evading Capture by Residual Disease Monitoring: Extramedullary Manifestation of JAK2 V617F-Positive Primary Myelofibrosis After Allogeneic Stem Cell Transplantation. (9th August 2015) - Langabeer, Stephen E.; Nolan, James; Haslam, Karl; Clarke, Lindsey; Flavin, Richard; Conneally, Eibhlin
Abstract : Monitoring of the JAK2 V617F allele burden in myeloproliferative neoplasms after allogeneic stem cell transplantation is useful to determine levels of residual disease and has the potential to detect early relapse and guide subsequent clinical intervention. A case is described of a JAK2 V617F-positive primary myelofibrosis patient who underwent allogeneic stem cell transplantation. Prospective residual disease monitoring of the peripheral blood failed to detect an extramedullary manifestation of the disease, a periorbital myeloid sarcoma, arising nearly three years after transplant. This case serves to highlight a pitfall in residual disease monitoring for myeloproliferative neoplasm-associated mutations in the post-allogeneic stem cell transplantation setting.